Longitudinal advocacy training for medical students: a virtual workshop series (Canadian Medical Education Journal, 2022)
Implication StatementAdvocacy curricula in Canadian medical schools vary significantly. Expert-led, interactive workshops can effectively teach students how to address social determinants of health and advocate for patients. The Longitudinal Advocacy Training Series (LATS) is a free-of-charge, virtual program providing advocacy training created for Canadian medical students by students. The program was straightforward to implement and had high participation rates with 1140 participants representing 9.7% of enrolled Canadian medical students. As well, the program had high satisfaction reported by 87.6% of participants. The LATS toolkit enables health professional programs to develop similar programs for empowering effective health advocates.